Cost effective proposal to produce clinical engineering professional to sustain the health care services of developing countries such as Bangladesh - Md. Anwar, Hossain; Mohiuddin, Ahmad; Md. Rafiqul, Islam; Md. Abdur, Rashid (2015)
In the recent years, health care services come under spotlight of the Clinical Engineering Professional. Hence developed countries produce skilled clinical engineers to sustain their health care management since past about 35 years as well as most developing countries. However, economically fluctuating developing countries such as Bangladesh could not produce skilled clinical engineers due to lack of awareness and high cost. As the results, most of the developed countries such as Bangladesh could sustain the standard health care services. This paper illustrates an economical approach to produce the skilled clinical engineers to improve the present health care services which faces lots of problems. Our proposal will be more cost effective to produce skilled clinical engineers for the benefit of health care services. The clinical engineers are the costly potential resources for the health care technology to sustain the health care services among the health care technology personnel. We firmly believe that the current ideas of the health care planers, health policy makers and health stakeholders about clinical engineers will be clear. Public and private hospitals will be encouraged to produce and introduce skilled clinical engineers.